Collected Works of Erasmus : Expositions of the Psalms, Volume 63 - Erasmus, Desiderius (Book collections on Project MUSE., 1998)
Erasmus stresses the role of the psalms as a comfort in tribulation and an exhortation to piety - in the very specific meaning that he gives to that word. He remains ever concerned about how the psalms relate to each individual in the conduct of his or her life.